Implementation of fuzzy logic control on a new low cost semi-active vehicle shock absorber - Ossama Mokhiamar; M. Ghoniem; T. Awad (Journal of Mechanical Engineering and Sciences, 2022)
This work implements a fuzzy logic control (FLC) on a proposed new low-cost semi-active shock absorber to improve vehicle ride comfort. The ordinary passive shock absorber is replaced with a new apparatus consisting of a conventional hydraulic cylinder with a proportional throttle valve placed outside the cylinder between its ports. FLC is used to adjust the damping coefficient by regulating the valve opening region. The fuzzy logic controller is configured using acceleration driven damping (ADD) methodology. Inputs are the accelerations of the sprung and the un-sprung masses, while the opening region of the valve is the output of the controller. Simscape/Matlab is used to build the model of the suggested semi-active shock absorber. The magneto-rheological (MR) suspension system and the suggested semi-active shock absorber with artificial neural network (ANN) controller are provided for comparison purposes. The findings demonstrated superior performance for the suggested shock absorber controlled by FLC relative to other controllers and to the ordinary damper as well, with one fourth of the cost of the magneto-rheological (MR) damper.